A Correlation between Parenting Styles and Mental Health in Adolescents at SMKN 2 Argamakmur - Dayati, Merry; Tranado, Hengki; Aprianti , Delta (Journal of Nursing, 2026)
Mental health is a condition in which individuals can understand their potential, work well, cope with stress, and contribute to their community. WHO data (2020) reports that the global prevalence of mental health problems among people aged 10-19 has increased by 16%, with this age group being the most vulnerable to mental health problems. The purpose of this study is to examine a correlation between parenting styles and mental health among adolescents at SMKN 2 Argamakmur. This study used total random sampling techniques and obtained a sample size of 76 respondents. Data collection was conducted using questionnaires on adolescent mental health and parenting styles. Based on the results of univariate analysis, it is found that the majority of respondents had good mental health (64,5%) and a small number of respondents had permissive parenting (48,7%). Bivariate analysis showed a p-value of < 0.05, namely 0.001, which means that there is a correlation between parenting styles and mental health among adolescents at SMKN 2 Argamakmur. The researcher suggests that teachers and staff at SMKN 2 Argamakmur understand how parenting styles affect students' mental health and behavior. This will help teachers recognize signs of mental health disorders related to parenting styles at home.